G Protein-Coupled Receptors as Potential Intercellular Communication Mediators in Trypanosomatidae - Díaz, Emilia; Febres, Anthony; Giammarresi, Michelle; Silva, Adrian; Vanegas, Oriana; Gomes, Carlos; Ponte-Sucre, Alicia (Frontiers in Cellular and Infection Microbiology, 2022)
Detection and transduction of environmental signals, constitute a prerequisite for successful parasite invasion; i.e., Leishmania transmission, survival, pathogenesis and disease manifestation and dissemination, with diverse molecules functioning as inter-cellular signaling ligands. Receptors [i.e., G protein-coupled receptors (GPCRs)] and their associated transduction mechanisms, well conserved through evolution, specialize in this function. However, canonical GPCR-related signal transduction systems have not been described in Leishmania, although orthologs, with reduced domains and function, have been identified in Trypanosomatidae. These inter-cellular communication means seem to be essential for multicellular and unicellular organism’s survival. GPCRs are flexible in their molecular architecture and may interact with the so-called receptor activity-modifying proteins (RAMPs), which modulate their function, changing GPCRs pharmacology, acting as chaperones and regulating signaling and/or trafficking in a receptor-dependent manner. In the skin, vasoactive- and neuro- peptides released in response to the noxious stimuli represented by the insect bite may trigger parasite physiological responses, for example, chemotaxis. For instance, in Leishmania (V.) braziliensis, sensory [Substance P, SP, chemoattractant] and autonomic [Vasoactive Intestinal Peptide, VIP, and Neuropeptide Y, NPY, chemorepellent] neuropeptides at physiological levels stimulate in vitro effects on parasite taxis. VIP and NPY chemotactic effects are impaired by their corresponding receptor antagonists, suggesting that the stimulated responses might be mediated by putative GPCRs (with essential conserved receptor domains); the effect of SP is blocked by [(D-Pro 2, D-Trp7,9]-Substance P (10-6 M)] suggesting that it might be mediated by neurokinin-1 transmembrane receptors. Additionally, vasoactive molecules like Calcitonin Gene-Related Peptide [CGRP] and Adrenomedullin [AM], exert a chemorepellent effect and increase the expression of a 24 kDa band recognized in western blot analysis by (human-)-RAMP-2 antibodies. In-silico search oriented towards GPCRs-like receptors and signaling cascades detected a RAMP-2-aligned sequence corresponding to Leishmania folylpolyglutamate synthase and a RAMP-3 aligned protein, a hypothetical Leishmania protein with yet unknown function, suggesting that in Leishmania, CGRP and AM activities may be modulated by RAMP- (-2) and (-3) homologs. The possible presence of proteins and molecules potentially involved in GPCRs cascades, i.e., RAMPs, signpost conservation of ancient signaling systems associated with responses, fundamental for cell survival, (i.e., taxis and migration) and may constitute an open field for description of pharmacophores against Leishmania parasites.